2021
DOI: 10.16995/glossa.5761
|View full text |Cite
|
Sign up to set email alerts
|

Failed gender agreement in L1 English L2 Spanish: Syntactic or lexical problem?

Abstract: According to representational accounts (Hawkins & Franceschina, 2004), the inability to acquire abstract syntactic features after a critical period explains L2 difficulties with gender, while according to lexical accounts (Grüter et al. 2012; Hopp 2012), gender assignment issues – the inability to assigned to a target-like class accounts for these difficulties. We explore three potential agreement cues: 1) semantic gender relating to sex (e.g. ‘girl’ vs. ‘boy’) 2) morphophonological transparency cues, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Behavioral L2 studies revealed that higher L2 proficiency facilitated L2 prediction based on morphosyntactic associations (e.g., Sagarra et al, 2021;Henry et al, 2022;see Ito and Pickering, 2021, for a review; and see Mitsugi, 2020, for lack of proficiency effects), phonosemantic associations (Perdomo and Kaan, 2021, for bin 5), and morphophonological associations (Sagarra and Casillas, 2018). Higher L2 proficiency also benefited L2 morphosyntactic processing (see 10.3389/fpsyg.2023.1141174 Frontiers in Psychology 14 frontiersin.org Kirova and Camacho, 2021, for a review), as well as L2 morphological processing (Kimppa et al, 2019), L2 word activation (Berghoff et al, 2021), and L2 phonological processing (Jun and Oh, 2000;White et al, 2015;Konishi et al, 2018;Maddah and Reiterer, 2018). Neurocognitive L2 studies indicated that higher L2 proficiency facilitated L2 morphosyntactic processing (see Alemán , for a review) and shaped the brain , allowing learners to activate the same brain areas as monolinguals (Vingerhoets et al, 2003).…”
Section: The Effects Of Language Proficiencymentioning
confidence: 99%
“…Behavioral L2 studies revealed that higher L2 proficiency facilitated L2 prediction based on morphosyntactic associations (e.g., Sagarra et al, 2021;Henry et al, 2022;see Ito and Pickering, 2021, for a review; and see Mitsugi, 2020, for lack of proficiency effects), phonosemantic associations (Perdomo and Kaan, 2021, for bin 5), and morphophonological associations (Sagarra and Casillas, 2018). Higher L2 proficiency also benefited L2 morphosyntactic processing (see 10.3389/fpsyg.2023.1141174 Frontiers in Psychology 14 frontiersin.org Kirova and Camacho, 2021, for a review), as well as L2 morphological processing (Kimppa et al, 2019), L2 word activation (Berghoff et al, 2021), and L2 phonological processing (Jun and Oh, 2000;White et al, 2015;Konishi et al, 2018;Maddah and Reiterer, 2018). Neurocognitive L2 studies indicated that higher L2 proficiency facilitated L2 morphosyntactic processing (see Alemán , for a review) and shaped the brain , allowing learners to activate the same brain areas as monolinguals (Vingerhoets et al, 2003).…”
Section: The Effects Of Language Proficiencymentioning
confidence: 99%
“…Behavioral L2 studies revealed that higher L2 proficiency facilitated L2 prediction based on morphosyntactic associations (e.g., Lew-Williams and Fernald, 2010;Dussias et al, 2013;Sagarra et al, 2021;Henry et al, 2022;see Ito and Pickering, 2021, for a review; and see Mitsugi, 2020, for lack of proficiency effects), phonosemantic associations (Perdomo and Kaan, 2021, for bin 5), and morphophonological associations (Sagarra and Casillas, 2018). Higher L2 proficiency also benefited L2 morphosyntactic processing (see 10.3389/fpsyg.2023.1141174 Frontiers in Psychology 14 frontiersin.org Kirova and Camacho, 2021, for a review), as well as L2 morphological processing (Kimppa et al, 2019), L2 word activation (Berghoff et al, 2021), and L2 phonological processing (Jun and Oh, 2000;White et al, 2015;Konishi et al, 2018;Maddah and Reiterer, 2018). Neurocognitive L2 studies indicated that higher L2 proficiency facilitated L2 morphosyntactic processing (see Alemán Bañón et al, 2018, for a review) and shaped the brain (Pliatsikas et al, 2020), allowing learners to activate the same brain areas as monolinguals (Vingerhoets et al, 2003).…”
Section: The Effects Of Language Proficiencymentioning
confidence: 99%